Forecasting the Gold Price of LM Antam using the Double Exponential Smoothing Approach - Mandati, Sri Amalia; Poniman; Novianti, Triuli (Tibuana, 2025)
Abstract— Antam Precious Metal (LM) gold investment is one of the investment choices favored by the public from the many investment choices available. One of the things that must be done if you want to invest in gold is to monitor the price movement of Antam Gold. This study uses the Double Method approach Exponential Smoothing with software Minitab 20. Double Method Exponential Smoothing is one of the forecasting methods used for trending data patterns . The gold price data to be forecasted is Antam Precious Metal (LM) gold produced by PT Antam Tbk. The purpose of this study is to obtain a forecast of Antam LM gold prices for the next twelve months from September 2024 to August 2025. The results of the study for the next twelve months the highest price forecast from September 2024 to August 2025 is in August 2025. The price of Antam gold in August 2025 is IDR 1,806,990 and the forecast error value (MAPE) is 2.31% or has a forecast accuracy of 97.69%.